ANALISA KONSUMSI DAYA SISTEM PELACAKAN POSISI MUATAN ROKET BERBASIS ARDUINO - Rama Windhu Putra, Anak Agung Bagus; Wiharta, Dewa Made; Putra Sastra, Nyoman (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUM, 2018)
This study examines the power consumption of the Arduino-based rocket payload position tracking system. The system device consists of Arduino Mega 2560, Sensor Compass, Barometer Sensor, GPS (Global Positioning System) Sensor, LCD (Liquid Crystal Display) character, Xbee-Pro 900HP, and two servo motors. Testing is done using a Digital Watt Meter tool that is able to read the voltage, current, and power used in the system. Test method by observing digital watt meter when the system runs tracking the rocket payload. Data retrieval interval is once every 10 minutes for 1 hour and calculates usage time, until the battery reaches the maximum usage limit. This research has been carried out successfully. When test performs on interval of 1 hour, the power usage by the system is 0.470 Ah until the battery voltage reaches 11.8 volts and the average power reaches 5.56 watts. Usage time of a Li-Po 1300 mAh battery is 3 hours 56 minutes until the battery voltage reaches 10.08 volts.